Motif Menonton Youtube Nihongo Mantappu Di Kalangan Remaja Kota Denpasar - Pramudita, Galuh; Suryawati, I Gusti Agung Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2023)
Youtube nihongo mantappu is a content creator making videos about educations and entertainment vlogs. This study aims to determine the motives for watching youtube nihongo mantappu among teenagers in Denpasar city. The reason Dennis McQuail suggested as a reason for media consumption is the reason used in this study. The theory of uses and gratifications, which employs quantitative descriptive methodologies, is the one applied in this study. In this study, a likert scale was employed to distribute questionnaires and gather data, and a purposeful sampling technique was used for the sample approach. The descriptive analysis method that was employed revealed that teens in Denpasar City watch YouTube nihongo mantappu for entertainment reasons by examining the average score of motives.